2000
DOI: 10.1097/00006454-200005000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin for treatment of tularemia in children

Abstract: In our sample of 12 patients ciprofloxacin was satisfactory for outpatient treatment of tularemia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 28 publications
2
48
0
5
Order By: Relevance
“…İlk çalışmalarda kinolonların immatür hayvanlarda atropati gelişimine neden olduğu için kinolonların 16 yaş altında kullanılması kontrindikasyon olarak kabul edilmiştir (4,7,8,43). Ancak, günümüzde iskelet sistemine yöne-lik bu riskin insanlarda çok düşük olduğu kabul edilmektedir.…”
Section: Kinolonlarunclassified
See 2 more Smart Citations
“…İlk çalışmalarda kinolonların immatür hayvanlarda atropati gelişimine neden olduğu için kinolonların 16 yaş altında kullanılması kontrindikasyon olarak kabul edilmiştir (4,7,8,43). Ancak, günümüzde iskelet sistemine yöne-lik bu riskin insanlarda çok düşük olduğu kabul edilmektedir.…”
Section: Kinolonlarunclassified
“…ABD'de siprofloksasin ve diğer kinolonların tularemi tedavisinde kullanımı ABD Gıda ve İlaç Dairesi (FDA) tarafından onaylanmamıştır (7). Kinolon tedavisinde başarısızlık, hipersensitivite reaksiyonu nedeniyle tedavinin erken sonlandırılması ve tedaviye geç başlanmasına bağlı lenfadenopatilerde süpürasyon gelişimi olarak bildirilmiştir (43,46).…”
Section: Kinolonlarunclassified
See 1 more Smart Citation
“…The first clinical reports from Scandinavia exhibited excellent response among both children and adults with tularemia [28,29]. Perez-Castrillon et al [13] have revealed that the efficacy of ciprofloxacin was higher than that of streptomycin or doxycycline and was associated with fewer adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin has also been utilized to treat tularemia in children. In a case series of 12 children, ciprofloxacin was effective, except when it was discontinued before completing a 10-day course due to the development of a rash [78]. Case reports also describe the successful use of levofloxacin for the treatment of tularemia [79,80].…”
Section: Review Hepburn and Simpsonmentioning
confidence: 99%